WACANA SEWAKA DHARMA DALAMGEGURITAN BHIMA SWARGA KAJIAN; SEMIOTIKA - Swastya Darma Pradnyan, I Gusti Made; Suastika, I Made; Jirnaya, I Ketut (JOURNAL OF LANGUAGE AND TRANSLATION STUDIES, 2016)
AbstractThis research is analysis of semiotic about the Sewaka Dharma discourse that contained implicitly and explicitly in Geguritan Bhima Swarga(GBS). Sewaka Dharma Constitute a dedication who do sincerely, 1) Restore the essence of understanding discourse in the literary creation so it doesn’t make miss understanding between discourse in the literary creation with art staging literary creation that identicaly Ruatan discourse in the human community, 2) Give a comprehension to the reader a illustration of discourse Sewaka Dharma in the literary creation, 3) Give a contribution to reaserch substantione specially about analysis of semiotic’s Peirce.The analysis result showing that, GBS was only contained a discourse ruatan in the human community, be evidenced by two formation of Sewaka Dharma discourse that is Madhawa SewaandManawa Sewa, from the function side basicly bay the six language function’s Roman Jakobson Such as, emotif function, konatif, referensial, fatic, metalingual and puitic. With the significant side, GBS contained diverse of significant refer’s to Madhawa Sewa and Manawa Sewa such as, The God significant, environment, individual, family, culture sociality, and country.ABSTRAKPenelitian ini merupakan kajian Semiotika tentang Wacana Sewaka Dharma yang terkandung secara implisit dan eksplisit dalam Geguritan Bhima Swarga(GBS).Sewaka Dharma merupakan sebuah pengabdian yang dilakukan secara tulus ikhlas. Tujuan penelitian ini adalah 1) Mengembalikan esensi pemahaman wacana yang terdapat dalam karya sastra sehingga tidak terjadi kerancuan antara wacana dalam karya sastra yang diidentikan dengan wacana ruatan dimasyarakat, 2) Memberikan pemahaman terhadap pembaca mengenai gambaran Wacana Sewaka Dharma dalam karya sastra, 3) Memberi sumbangan terhadap khasanah penelitian khususnya mengenai penerapan kajian semiotika Peirce.Hasil analisis menunjukan bahwa, Geguritan Bhima Swarga yang pada awalnya hanya terkandung sebuah Wacana Ruatan di Masyarakat,terbukti terdapat dua bentuk Wacana Sewaka Dharma yaitu Madhawa Sewa dan Manawa Sewa, selanjutnya dari segi fungsi mengacu pada enam fungsi bahasa Roman Jakobson yaitu, fungsi Emotif, Konatif, Refrensial, Fatik, Metalinguistik dan Puitik. Terkait dengan makna, dalam Geguritan Bhima Swarga terkadung beragam makna yang mengacu pada Madhawa Sewa dan Manawa Sewa diantaranya, Ruang Lingkup Ketuhanan, Lingkungan, Individu, Keluarga, Sosial Budaya, dan Negara.